2012
DOI: 10.1136/archdischild-2011-301074
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of four cases of meningococcal disease in a single nuclear family

Abstract: A cluster of four confirmed cases of meningococcal disease was seen in the same nuclear family across a 15-week period. The cases were three siblings and a parent and all recovered well. The first case was confirmed by meningococcal PCR only but the subsequent three cases were due to indistinguishable strains of serogroup B (B:NT:P1.19-1,15-11). Contact tracing was initially undertaken and reviewed in detail after each subsequent case. Antibiotic prophylaxis was administered to close family contacts on three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…34 MenB disease has also been the cause of recent outbreaks at college campuses in the United States, 47 outbreaks in nursery and high schools, [48][49][50] cluster of disease in Europe. 51 An increase in MenW disease owing to endemic expansion of a single type cc11 has been observed across all age groups in England, Wales, and the Netherlands. 12,52,53 In England and Wales, among those aged 5 to 19 years, cases of MenW cc11 increased from 3 in 2008/ 2009 to 15 in 2013/2014 compared with 21 in 2008/2009 and 98 in 2013/2014 across all ages.…”
Section: Epidemiology Of Meningococcal Diseasementioning
confidence: 99%
“…34 MenB disease has also been the cause of recent outbreaks at college campuses in the United States, 47 outbreaks in nursery and high schools, [48][49][50] cluster of disease in Europe. 51 An increase in MenW disease owing to endemic expansion of a single type cc11 has been observed across all age groups in England, Wales, and the Netherlands. 12,52,53 In England and Wales, among those aged 5 to 19 years, cases of MenW cc11 increased from 3 in 2008/ 2009 to 15 in 2013/2014 compared with 21 in 2008/2009 and 98 in 2013/2014 across all ages.…”
Section: Epidemiology Of Meningococcal Diseasementioning
confidence: 99%
“…Family clusters have also been described in the literature but their time duration is considerably shorter than our outbreak [24].…”
Section: Discussionmentioning
confidence: 46%
“…Others have reported a cluster of cases over a long timescale, e.g. Acheson et al [12], but this was within a single nuclear family, a setting where there is a higher risk of secondary cases. The authors concluded that it was likely that the strain was reintroduced by a regular non-household contact or unidentified close contact [12].…”
Section: Introductionmentioning
confidence: 96%
“…Acheson et al [12], but this was within a single nuclear family, a setting where there is a higher risk of secondary cases. The authors concluded that it was likely that the strain was reintroduced by a regular non-household contact or unidentified close contact [12]. In addition, Mandal et al reported an outbreak of 13 cases between January 2008 and November 2010 [13].…”
Section: Introductionmentioning
confidence: 98%